Cystic Shape Cemento-Ossifying Fibroma of Ethmoid Sinus - Dražen Shejbal; Gabrijela Vonsović; Tomislav Baudoin; Davor Vagić (Acta Stomatologica Croatica, 2015)
Cemento-ossifying fibromas are a group of rarely occurring benign tumours, developing from the periodontal membrane and varying considerably in appearance and in the progress of the disease. Their common feature is higher or lower production of cemental tissue. In most cases the tumours are small because their cementoma mature quickly and become inactive, which causes the tumour to stop growing. They develop most frequently in the mandible and also in the maxilla. Other sites, such as paranasal cavities, soft tissues and bones of the head, are extremely rare. The case of a cemento-fibrosing tumour with psammoma infiltrations, developing from the ethmoid sinus in a nine-year-old girl is reported. Due to frontal headaches and sight defects as well as impaired vision on the right side, NMR was done, which showed a mucocele of the front and rear ethmoid with destruction of the orbital wall and a breakthrough into the orbit. The right maxillary sinus showed a visible retention and a thickened mucous membrane. A rhinoscopy revealed a ball-shaped spherical mass in the medial nasal meatus, which was defined as concha bullosa. An endoscopic examination showed that the tumour protruded in front of the medium nasal concha into the right nasal cavity, softened the ethmoid roof, penetrated toward the base of the skull, adhered and pushed the orbit. It was removed by FESS technique, and PHD revealed subsequently that it was not a mucocele but a cemento-ossifying fibroma.